2019
DOI: 10.1021/acs.jmedchem.8b01709
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Poly(ADP-ribose) Polymerase Inhibitors: Impact of Adenosine Pocket-Binding Motif Appendage to the 3-Oxo-2,3-dihydrobenzofuran-7-carboxamide on Potency and Selectivity

Abstract: To evaluate interrater agreement in categorizing treatment outcomes and drug responsiveness status according to the International League Against Epilepsy (ILAE) definition of drug-resistant epilepsy. Methods: A total of 1053 adults with focal epilepsy considered by the investigators to meet ILAE criteria for drug resistance were enrolled consecutively at 43 centers and followed up prospectively for 18-34 months. Treatment outcomes for all antiepileptic drugs (AEDs) used up to enrollment (retrospective assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…Such inhibitor-induced changes would also be expected to be relevant to understanding activation. The great majority of PARP inhibitors mimic only the nicotinamide moiety of PARP’s natural substrate NAD + , and it has previously been shown that a non-hydrolysable analogue of NAD + (benzamide adenine dinucleotide, BAD), which includes also the adenosine moiety, is incapable of binding to isolated PARP-1 CAT domain unless the HD subdomain is deleted ( 19 ); in addition, a series of inhibitors designed to reach into the adenosine binding pocket were all similarly unable to bind to the isolated, intact CAT domain ( 20 ). In light of such observations, the autoinhibitory blockade of catalysis caused by the HD subdomain, and which is relieved during activation, is hypothesised to be primarily a steric barrier to binding of the adenosine moiety of NAD + .…”
Section: Introductionmentioning
confidence: 99%
“…Such inhibitor-induced changes would also be expected to be relevant to understanding activation. The great majority of PARP inhibitors mimic only the nicotinamide moiety of PARP’s natural substrate NAD + , and it has previously been shown that a non-hydrolysable analogue of NAD + (benzamide adenine dinucleotide, BAD), which includes also the adenosine moiety, is incapable of binding to isolated PARP-1 CAT domain unless the HD subdomain is deleted ( 19 ); in addition, a series of inhibitors designed to reach into the adenosine binding pocket were all similarly unable to bind to the isolated, intact CAT domain ( 20 ). In light of such observations, the autoinhibitory blockade of catalysis caused by the HD subdomain, and which is relieved during activation, is hypothesised to be primarily a steric barrier to binding of the adenosine moiety of NAD + .…”
Section: Introductionmentioning
confidence: 99%
“…5). We note that the crystallographic poses of several other PARPis position piperazine moieties at alternate locations [19,[66][67][68]. For example, the crystal structure of the potent PARPi EB 47 [69,70] bound to PARP16 (PDB ID: 6HXR) places a piperazine substructure near that of our compound 5 docked pose.…”
Section: Parpi Lead-optimization Runs Autogrow4 Applied To Lead Optimmentioning
confidence: 89%
“…5c). These interactions are typical of the binding modes of known PARPi [18][19][20][58][59][60][61][62][63][64][65][66] such as the crystallographic olaparib pose (Fig. 5a) [19] and a docked CEP-9722 pose (Cephalon, Fig.…”
Section: Parpi Lead-optimization Runs Autogrow4 Applied To Lead Optimmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, SA and QED scores of A_sample1 (0.65 and 0.56 respectively) are better than those of Compound 3 (0.54 and 0.51). Visual inspection reveals that A_sample1 conserves the π-π stacking interaction with Y907 and Y896 and the hydrogen bond with G863 that are well known binding interactions [29][30][31][32][33][34][35][36] . In addition, the interacting residues H862 and Y896 are well conserved residues from PARP-1 to PARP-6 37 .…”
Section: Analysis Of Docking Posesmentioning
confidence: 99%